2022
DOI: 10.1177/19714009221122204
|View full text |Cite
|
Sign up to set email alerts
|

Mapping early tumor response to radiotherapy using diffusion kurtosis imaging**

Abstract: Purpose In this pilot study, DKI measures of diffusivity and kurtosis were compared in active tumor regions and correlated to radiologic response to radiotherapy after completion of 2 weeks of treatment to derive potential early measures of tumor response. Methods MRI and Magnetic Resonance Spectroscopic Imaging (MRSI) data were acquired before the beginning of RT (pre-RT) and 2 weeks after the initiation of treatment (during-RT) in 14 glioblastoma patients. The active tumor region was outlined as the union of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…Nonetheless, we can point to a few recent examples where the measurement of directional kurtosis has clear advantages. A study on mapping tumour response to radiotherapy treatment found axial kurtosis to provide the best sensitivity to treatment response (Goryawala et al, 2022 ). In a different study a correlation was found between glomerular filtration rate and axial kurtosis is assessing renal function and interstitial fibrosis (Li et al, 2022a ).…”
Section: Extension To Directional Kurtosismentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, we can point to a few recent examples where the measurement of directional kurtosis has clear advantages. A study on mapping tumour response to radiotherapy treatment found axial kurtosis to provide the best sensitivity to treatment response (Goryawala et al, 2022 ). In a different study a correlation was found between glomerular filtration rate and axial kurtosis is assessing renal function and interstitial fibrosis (Li et al, 2022a ).…”
Section: Extension To Directional Kurtosismentioning
confidence: 99%
“…Recent clinical benefits of using kurtosis metrics over other DW-MRI derived measures have been demonstrated for grading hepatocellular carcinoma (Li et al, 2022b ), prognosing chronic kidney disease (Liu et al, 2021 ), differentiating parotid gland tumours (Huang et al, 2021a ), measuring response to radiotherapy treatment in bone tumour (Guo et al, 2022a ) and glioblastoma (Goryawala et al, 2022 ), identifying tissue abnormalities in temporal lobe epilepsy patients with sleep disorders (Guo et al, 2022b ) and brain microstructural changes in mild traumatic brain injury (Wang et al, 2022 ), monitoring of renal function and interstitial fibrosis (Li et al, 2022a ), detecting the invasiveness of bladder cancer into muscle (Li et al, 2022d ), aiding management of patients with depression (Maralakunte et al, 2022 ), delineating acute infarcts with prognostic value (Hu et al, 2022 ), predicting breast cancer metastasis (Zhou et al, 2022 ), diagnosing Parkinson's disease (Li et al, 2022c ), amongst others reported prior and not listed here.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, with improved characterizations of the biological response of tumors to treatment methods, particularly, radiotherapy with immunomodulatory effects, advanced and efficacious therapeutic strategies might be developed. In clinical attempts and preclinical studies, several biological imaging techniques, such as diffusion kurtosis imaging 137 , multi-parametric MRI 138 , and highly sensitive whole-body PET/SPECT or optical imaging 139 , have been trialed or tested to assess early tumor response to radiotherapy, concentrating on the level of cellular communities and acellular components.…”
Section: Biomarker-driven Molecular Imaging Probes In Radiotherapy Wo...mentioning
confidence: 99%